The Long-Run Educational Benefits of High-Achieving Classrooms - Serena Canaan; Pierre Mouganie; Peng Zhang (Institute of Labor Economics (IZA), 2022)
Despite the prevalence of school tracking, evidence on whether it improves student success is mixed. This paper studies how tracking within high school impacts high-achieving students' short- and longer-term academic outcomes. Our setting is a large and selective Chinese high school, where first-year students are separated into high-achieving and regular classrooms based on their performance on a standardized exam. Classrooms differ in terms of peer ability, teacher quality, class size, as well as level and pace of instruction. Using newly collected administrative data and a regression discontinuity design, we show that high-achieving classrooms improve math test scores by 23 percent of a standard deviation, with effects persisting throughout the three years of high school. Effects on performance in Chinese and English language subjects are more muted. Importantly, we find that high-achieving classrooms substantially raise enrollment in elite universities, as they increase scores on the national college entrance exam—the sole determinant of university admission in China.
Keywords: I21; I24; I26; J24; 330; classroom tracking; peer quality; teacher quality; regression discontinuity; China